STRUCTURAL AWARENESS AS SHARED INTERPRETIVE COMPETENCE IN DUO PERFORMANCE - PREDA-ULITA, Anca (Studia Universitatis Babes-Bolyai Musica, 2026)
This study examines structural awareness as a shared interpretive competence in duo performance. Rather than treating analysis as an individual cognitive tool, it frames structural awareness as a relational process emerging through coordination between performers. Duo performance is approached as an interpretive system in which form is negotiated in real time, shaping phrasing, agogics, articulation, and expressive timing. Selected examples (violin–piano, clarinet–piano, voice–piano) show how shared structural reference points guide interpretive decisions and support advanced chamber-music practice.